The SDG-Islamic Banking Nexus: Insights from the OIC Top Economies - Basalma, Ebrahim Omar (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
ABSTRACT – Islamic Banking and Finance (IBF) has emerged as a promising alternative to conventional finance, with its principles aligned with the United Nations' Sustainable Development Goals (SDGs). This study investigates the relationship between the performance of IBF in five major Organization of Islamic Cooperation (OIC) countries - Saudi Arabia, Turkey, Indonesia, Malaysia, and the United Arab Emirates - and key SDG indicators: return on assets, regulatory capital to assets, regulatory Tier 1 capital to risk-weighted assets, and broad money to total reserves ratio. Employing panel data analysis, the research reveals that three out of the four SDG indicators significantly impact the total assets of Islamic banks, while the regulatory capital-to-assets indicator shows no significant relationship. These findings underscore the complex interplay between profitability, risk management, liquidity, and asset growth in the IBF sector. The study contributes to the growing body of literature on the role of IBF in promoting sustainable development. The results have important implications for regulators, policymakers, and Islamic banking institutions, highlighting the need for a balanced approach that reconciles financial performance with social and environmental objectives. By aligning IBF with the SDGs, this research paves the way for a more sustainable and inclusive financial system that can drive economic growth, social welfare, and environmental sustainability in the Muslim world and beyond.========================================================================================================ABSTRAK – Hubungan SDG dengan Perbankan Syariah: Wawasan dari Negara-Negara Utama OKI. Perbankan dan Keuangan Syariah telah menjelma menjadi alternatif yang menjanjikan bagi keuangan konvensional, dengan prinsip-prinsipnya yang selaras dengan tujuan pembangunan berkelanjutan (SDGs). Penelitian ini menyelidiki hubungan antara kinerja total aset perbankan dan keuangan Islam di lima negara utama OKI, yaitu Saudi Arabia, Turkey, Indonesia, Malaysia, and the United Arab Emirates, dan beberapa indikator SDG yaitu laba atas aset, modal peraturan terhadap aset, peraturan modal Tier 1 terhadap aset tertimbang menurut risiko, dan uang beredar terhadap total cadangan. Studi ini menggunakan pendekatan analisis data panel yang mengumpulkan regresi kuadrat terkecil biasa menggunakan data sepuluh tahun dari tahun 2013 hingga 2022. Hasilnya menunjukkan bahwa tiga dari empat indikator SDG mempunyai dampak signifikan terhadap total aset perbankan syariah, sedangkan peraturan modal terhadap total aset perbankan syariah tidak berpengaruh signifikan terhadap total aset perbankan syariah. Temuan ini menunjukkan adanya trade-off antara profitabilitas, manajemen risiko, likuiditas, dan pertumbuhan aset di perbankan syariah. Temuan ini mempunyai implikasi bagi regulator, pembuat kebijakan, dan lembaga perbankan Islam, serta berkontribusi terhadap pemahaman keuangan yang bertanggung jawab dan pembangunan berkelanjutan.